2022
DOI: 10.1021/acsaem.1c03791
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-grafted-Gallic Acid as a Nature-Inspired Multifunctional Binder for High-Performance Silicon Anodes in Lithium-Ion Batteries

Abstract: Due to its high theoretical specific capacity and natural abundance, silicon (Si) and its composites are considered to be pivotal anode materials for high-energy-density next-generation lithium-ion batteries (LIBs). However, the significant volume changes during the repeated lithiation/delithiation process cause the loss of electrical contact and the continuous formation of a solid electrolyte interface (SEI), hindering Si’s practical applications. The rational design of the polymer binder is an efficient appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“… 1 , 5 , 13 17 Adding salt to polymers causes changes in the structure, and in optical, electrical, and thermal properties. 1 , 14 , 18 20 In the case of chitosan, it provides ions as charge carriers that can improve the conductivity of the polymer, as has been reported in different works. 1 , 21 , 22 The most used dopants in the preparation of many polymer electrolytes are lithium salts like lithium perchlorate, 19 , 23 , 24 lithium tetraborate, 25 lithium hexafluorophosphate, and lithium trifluoromethanesulfonate.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“… 1 , 5 , 13 17 Adding salt to polymers causes changes in the structure, and in optical, electrical, and thermal properties. 1 , 14 , 18 20 In the case of chitosan, it provides ions as charge carriers that can improve the conductivity of the polymer, as has been reported in different works. 1 , 21 , 22 The most used dopants in the preparation of many polymer electrolytes are lithium salts like lithium perchlorate, 19 , 23 , 24 lithium tetraborate, 25 lithium hexafluorophosphate, and lithium trifluoromethanesulfonate.…”
Section: Introductionmentioning
confidence: 85%
“…Many hydroxyls and amine groups in polymers can act as electron donors, facilitating the reactions with many organic and inorganic salts to form polyelectrolytes. ,, Adding salt to polymers causes changes in the structure, and in optical, electrical, and thermal properties. ,, In the case of chitosan, it provides ions as charge carriers that can improve the conductivity of the polymer, as has been reported in different works. ,, The most used dopants in the preparation of many polymer electrolytes are lithium salts like lithium perchlorate, ,, lithium tetraborate, lithium hexafluorophosphate, and lithium trifluoromethanesulfonate. , Lithium salts are preferred due to their low interfacial strength and ability to coordinate and solvate easily, exhibiting their ionic conductivity character. The advantage of incorporating these salts is that a complexation can be obtained when the polymer electrolytes are prepared due to their high dissociation energy and good solubility in most solvents …”
Section: Introductionmentioning
confidence: 99%
“…They can form strong interactions with electrolytes through hydrogen bonds or dipole interactions. To date, there have been many polymer binders, including polyacrylic acid (PAA), 76,79 sodium carboxymethyl cellulose (CMC), 80,81 sodium alginate (SA), 82 polyvinyl alcohol (PVA), 83 guar gum (GG), 84 etc., and bio-polysaccharided derived 54,59,85 with affluent -OH, COOH/COOR have been explored. These binders improve the interaction between its Si-based particles and mitigate the rupture of electrodes during charging and discharging.…”
Section: Grafted Polymer Bindersmentioning
confidence: 99%
“…Recently, numerous studies have confirmed that compared with the above linear structure binder, grafting or cross-linking network binders constructed by reasonably designed functional components can well adapt to the huge volume expansion of Si . Grafting modification can increase the active group or form a branched structure, , while cross-linking modification can form a three-dimensional (3D) network structure . These modification methods can reduce irreversible slippage of polymer chains, , thereby contributing to maintain the integrity of Si-based anodes.…”
Section: Introductionmentioning
confidence: 99%